Level of tax knowledge and perception of tax fairness among non-accounting students - Shuid, Siti Hawa; Ismail, Norhidayah; Abdul Jabar, Ja’izah; Azis, Saflina; Mat, Mustafa Kamal (2023)
Given the significant increase in digital transactions, the emphasis on the importance of voluntary tax compliance is still prevalent. Taxpayers and future taxpayers need to have tax knowledge to record these transactions on the tax return form. Hence, the objective of this study is to examine the level of tax knowledge and fairness perceptions of non-accounting students. This study was conducted using an online questionnaire with the participation of 112 students who were currently enrolled in diploma programs. The results show the respondents possess a satisfactory level of tax knowledge and perceive the tax system as fair. The outcome of this study could offer valuable insights for the government and tax authority to further enhance the present tax system and promote a higher degree of voluntary tax compliance. It also offers a signal to policymakers of the significance of tax knowledge in facilitating the development of tax education programs, particularly in early childhood education programs.